The Implementation of Service Guarantees in China Service and Manufacturing Industries - Tang, Lan (2011)
With the development of economy in the world, people would like to spend more money to enjoy their life. In this way, service industry becomes more popular than manufacturing industry. In addition, although the main business of a company is production, it will provide additional services, such as after-sales services, to increase its products’ selling volume. At the same time, a good service quality should be improved and guaranteed by applying service guarantee. However, China is a developing country, and service industry has developed for just a few years, so companies in China are not familiar with how to provide services to their customers to satisfy their needs and wants. As a result, the main topic of this dissertation is to investigate the drivers and risks of applying service guarantee in three different sectors-Healthcare, white goods, and hotel in China, and put forward the suitable types of service guarantees to these sectors by analysing three influencing factors (consumer behaviour, industry characteristics, and operational issues). In order to achieve above objectives, both empirical data and secondary data should be collected. In the literature review, the researcher used secondary data and found gaps which need to be filled through using evidences in the real world. The researcher found that almost all kinds of service guarantees can reduce purchasing risks and protect consumers’ rights. In addition, different kinds of service guarantees have different benefits. While, designing a good service guarantee is difficult, and it needs to consider many factors, and different companies need to design different service guarantees according to their conditions. At the same time, the researcher found that some Chinese consumer behaviours, such as collectivism and cheating, characteristics of manufacturing industry, such as product-related services, and operational issues, such as distribution channel and some specific operations in hotel are the obstacles of implementing service guarantee in China. In the empirical researches, Siemens Healthcare, Elekta, Siemens electronic household appliances, Hilton hotel, KUNLUN hotel were analysed to give the further in-depth understanding of theories in literature review and put forward evidences of previous statements. The main findings of researcher were that manufacturing companies should use conditional service guarantee which needs to base on customers’ requirements, while service companies should use unconditional service guarantee, but they also need to understand their customers to reduce risks. Key words: Service guarantee, conditional service guarantee, unconditional service guarantee, Chinese consumer behaviour, industry characteristics, operational issues.